Fabrication and characterization of polyaniline/carbon black VXC72/woven abaca composite for electromagnetic interference shielding application - Fernandez, Martin Guillermo C. (Animo Repository, 2023)
This research investigates the electromagnetic (EM) shielding capabilities of Polyaniline (PAni)-functionalized woven Abaca fibers, reinforced with Carbon Black (CB) VXC 72, in the ultrahigh frequency range (UHF) specifically in the 500 MHz to 4500 MHz as provided by the Vector Network Analyzer (VNA). The EM shielding performance of the composites were evaluated through a guided wave using the prescribed procedure indicated in the American Society for Testing and Materials (ASTM) D4935. The morphological profile and elemental analysis were investigated using SEM-EDX, and the functional groups of the composites were investigated using FTIR. The study also investigated the electrical resistivity of the composites using the Four-Point Probe Method. It was determined that the PAni/1CB/Abaca holds the least Resistivity at 891 Ω cm while 1CB/Abaca has the most at 5238 Ω cm. The functionalization of the fabrics was a success with imparting shielding properties on the previously nonshielding Abaca. Shielding Effectiveness (SE) of the composites reveal that PAni/1CB/Abaca has the highest mean SE with 5.96 dB which is around 74.34% of the EM wave has been attenuated. Selective EM shielding effect for samples with “2CB” at frequencies of 1417 MHz to 1890 MHz with 2CB/Abaca having a peak attenuation 8.26 dB at 1665 MHz and PAni/2CB/Abaca with 7.98 dB at 1687 MHz.